Advances in liver xenotransplantation. Issue 6 (December 2018) - Cimeno, Arielle; Barth, Rolf N.; LaMattina, John C.
Abstract : Purpose of review: This review highlights advances in liver xenotransplantation, focusing on immunologic barriers and mechanisms underlying graft failure and recipient demise, and discussion of recent in-vivo results. Recent findings: Pig to primate models of liver xenotransplantation have been plagued by thrombocytopenia, anemia, and coagulopathy. It is now known that platelet sequestration is mediated by liver sinusoidal endothelial cells and Kupffer cells in part by asialoglycoprotein receptor 1-driven mechanisms. Xenoantigens, specifically N-glycolylneuraminic acid, play a role in graft injury as well as red blood cell consumption. Finally incompatibilities between coagulation cascade molecules contribute to lethal coagulopathy, but can be counteracted with genetic modifications and coagulation factor supplementation. Survival has markedly increased with this strategy. Summary: An increased understanding of the cellular mechanisms responsible for failure of in-vivo pig to primate liver xenotransplant models has led to improved outcomes, and this recent success supports initial clinical application.